MENINGKATKAN MOTIVASI BELAJAR SISWA SELAMA PANDEMI COVID-19 MELALUI HIPNOTERAPI - Haryati, Tina (Balai Diklat Keagamaan Bandung, 2023)
The lack of student motivation to learn in the online learning process during the COVID-19 pandemic can be seen from students' passivity when participating in virtual learning and the reduction in student assignments at school. This research aims to increase students' learning motivation through hypnotherapy methods. The research subjects were 32 students. Data collection used interview techniques, observation and documentation studies with qualitative descriptive data analysis techniques. The results of this research indicate an increase in student learning motivation by 65%. The research results show that the hypnotherapy method can increase students' learning motivation during the Covid-19 pandemic. Thus, learning weaknesses during the pandemic can be corrected by using hypnotherapy, to increase students' learning motivation.